POTRET KEBERAGAMAN MASYARAKAT ARAB - Ismah; Ridlo, Abdullah (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2025)
The Arab society is known as a community rich in cultural, ethnic, linguistic, and religious diversity. This article aims to portray the dynamics of diversity within Arab society by examining various historical, social, and cultural aspects that shape both collective and local identities in the Arab world. This study employs a descriptive qualitative approach using the method of library research, analyzing relevant literature from various scholarly sources and historical documents. The findings indicate that although Arab society is often perceived as homogeneous due to shared language and religion, in reality, there exists significant diversity in religious practices, local traditions, social structures, and value systems. This diversity has been shaped by a long history of interaction with various civilizations, as well as differing geographical and political influences across regions. The study emphasizes the importance of understanding this diversity in order to strengthen intercultural dialogue and build social cohesion amidst the complexities of modern Arab identity.